Monitoring Irigasi Otomatis Berbasis IoT dan Android - Suwardoyo, Untung; Sanjani MK, Raf (Fakultas Teknik Universitas Muhammadiyah Parepare, 2025)
Irrigation management is still often done manually, especially in Pinrang Regency. Managing irrigation efficiently has challenges due to distance and unpredictable weather conditions. The purpose of this design is to make it easier to open and close irrigation doors through Android. The method used is an experimental method with a design using Internet of Things-based tools and Android applications. The test results show that the system prototype can operate the automatic irrigation gate according to the required water height and volume. The design proves that it can be an effective and efficient solution in irrigation management.